Diversity management practices in a multinational company in the pulp and paper sector - Maia, Lícia Serpa; Leopoldino, Cláudio Bezerra (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: Companies with limited diversity show weaker performance compared to inclusive organizations aligned with ESG (Environmental, Social, and Governance) principles, although this correlation may not apply universally. Despite these efforts, some diversity-related actions have been inadequate, incomplete, yielded unfavorable outcomes, or proved ineffective. Purpose: The present study aims to analyze the practices and actions adopted in the diversity management of a multinational in the Pulp and Paper sector. Method: The research employs a qualitative and descriptive methodology. It also features a case study. The data collection method employed was a semi-structured interview script. Five employees actively engaged in implementing the company's diversity and inclusion initiatives as ambassadors, all representing minority groups, were interviewed. Results: The company conducted various initiatives to promote diversity and inclusion, encompassing non-discrimination practices, support, and accountability measures. Most of these initiatives were deemed successful by interviewees. The study highlighted the benefits and challenges associated with diversity management practices, indicating progress towards the established goals. Simultaneously, certain practices impacted the personal lives of the participants, while external factors also influenced the outcomes and challenges faced. Conclusions: The identified practices, along with the reported benefits and challenges, contribute to diversity management and align with existing literature while also reflecting the unique aspects of the company under review, prompting further inquiry and potential future research.